Lonely Planet Thailand: Travelling in Thailand through the Eyes of Westerners - Chantrasupawong, Narumol (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This article aims at studying the "myth" the West subscribes to the East (Thailand, the Orient) in the Lonely Planet Thailand guidebook. The concept of 'myth' presented in Mythologies introduced by Roland Barthes, the concept of colonial discourse presented in Orientalism written by Edward Said together with the concepts of postcollonialism are applied in the study. Through descriptions of interesting tourist spots in Thailand, Lonely Planet uses vocabulary, expressions and illustrations to gradually, and seemingly unintentionally, construct Thailand in its readers' imagination. The 'myth' shown in the guidebook is that Thailand (the Orient) is inferior, unusual and bizarre while the West is 'inherently superior and civil'. However, Thailand (the Orient) has Fertile land with lush forests, large varieties of bird life and great marine life. Moreover, the 'myth' that the Orient is exotic, extraordinary and eccentric as well as that the Orient is feminine, tempting and sexually mysterious are also implicitly reinforced.